Guidelines for a palliative approach for aged care in the community setting: A suite of resources - Toye, Christine; Blackwell, S.; Maher, S.; Currow, D.; Holloway, Kristi; Tieman, J.; Hegarty, M. (Australasian Medical Journal Pty Ltd, 2012)
In Australia, many people ageing in their own homes are becoming increasingly frail and unwell, approaching the end of life. A palliative approach, which adheres to palliative care principles, is often appropriate. These principles provide a framework for proactive and holistic care in which quality of life and of dying is prioritised, as is support for families.